2015
DOI: 10.1186/s12882-015-0114-5
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the predictors of disease progression in patients with autosomal dominant polycystic kidney disease

Abstract: BackgroundAutosomal dominant polycystic kidney disease (ADPKD) is a genetic disorder characterised by progressive renal cyst formation leading to renal failure in the majority of patients. The likelihood and rate of ADPKD progression is difficult to predict and there is a clear need to identify prognostic indicators that could be used to anticipate ADPKD progression, to aid the management of patients in clinical practice.MethodsA systematic literature review was conducted to identify publications detailing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 76 publications
2
34
0
Order By: Relevance
“…To identify relationships between TKV, eGFR and available patient risk factors, exploratory analysis of patient-level data from the TEMPO 3:4 placebo arm (Table 1 ) was conducted using R version 2.12.2. Candidate prognostic variables assessed within a multivariable regression framework included those identified in the literature [ 10 ], agreed upon by clinical experts in ADPKD management, and available within the TEMPO 3:4 dataset: baseline age, gender, child bearing age, ethnicity, region, country, TKV (analysed at baseline, 12, 24 and 36 months) and eGFR (analysed at corresponding timepoints). Candidate variables were entered into the model simultaneously, and the step AIC approach [ 14 ] was used to identify candidate models and test for interactions between covariates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To identify relationships between TKV, eGFR and available patient risk factors, exploratory analysis of patient-level data from the TEMPO 3:4 placebo arm (Table 1 ) was conducted using R version 2.12.2. Candidate prognostic variables assessed within a multivariable regression framework included those identified in the literature [ 10 ], agreed upon by clinical experts in ADPKD management, and available within the TEMPO 3:4 dataset: baseline age, gender, child bearing age, ethnicity, region, country, TKV (analysed at baseline, 12, 24 and 36 months) and eGFR (analysed at corresponding timepoints). Candidate variables were entered into the model simultaneously, and the step AIC approach [ 14 ] was used to identify candidate models and test for interactions between covariates.…”
Section: Methodsmentioning
confidence: 99%
“…Early identification of ADPKD patients with rapidly progressing disease may facilitate the selection of those most likely to benefit from treatment in clinical trials and clinical practice; thus, improving the cost-effectiveness and benefit-to-risk ratio of novel therapies in a population with high unmet need [ 1 , 8 , 9 ]. A systematic literature review by Woon et al identified age at diagnosis and total kidney volume (TKV) as the most commonly cited prognostic indicators associated with rapid ADPKD progression [ 10 ]; additional factors reported in the literature include baseline GFR, male gender and PKD1 mutation [ 1 , 3 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The covariates adjusted for in the analysis included: age, gender, PKD genotype (PKD 1 or PKD 2), baseline systolic and diastolic BP, baseline BMI, baseline eGFR (for HtTKV analysis only), and baseline uACR. These variables were chosen for inclusion due to their strong epidemiologic associations with progression of disease in ADPKD [20].…”
Section: Covariatesmentioning
confidence: 99%
“…A number of studies have tried to identify markers that can predict rapid progression to ESRD in ADPKD [ 24 , 25 ]. Figure 1 shows that a wide variety of markers has been considered, but in the present article we will concentrate on those that are better validated (highlighted in Figure 1 ), bearing in mind that not all factors are independent.…”
Section: Evidence Of Rapid Disease Progressionmentioning
confidence: 99%